The Role of Government and Involvement of Muslim Community in Promoting Halal Organic Food Consumption Behavior - Ihsan Effendi; Lailan Tawila; Mitra Mustika Lubis (AL-TAHRIR, 2022)
The main problem for Muslim farmers in organic food production tends to be the marketing aspect. This requires the government's intervention and related stakeholders in the marketing of organic food. So far, Muslim farmer groups have not been able to be independent, especially in marketing organic agricultural products. This study aims to analyze the role of local government and the involvement of Muslim communities as organic food consumers in North Sumatra Province. This research was conducted using a sample of 270 respondents taken from a local market that sells organic food in North Sumatra. The results showed that the role of the involvement of the Muslim community and local government had a significant effect on the purchase of local organic food. This research also confirms the role of non-governmental organizations (NGOs) in forming a Muslim consumer community involved in marketing organic food.